Heterologous expression of the M. abscessus CBASS system confers phage TM4 resistance in M. smegmatis - Chun-Liang Wang; Ao-Fei Duan; Da-min Pan; Yi-Ou Zhao; Jian Yang; Yi-Cheng Sun (BMC Microbiology)
Abstract Phage therapy for multidrug-resistant Mycobacterium abscessus is constrained by the narrow lytic spectrum of phages due to unknown antiphage mechanisms. Bacteria deploy various defense strategies to prevent phage infection, but few have been comprehensively characterized in mycobacteria. Mycobacteriophage TM4 successfully delivers DNA into M. abscessus but fails to establish infection. Bioinformatic analyses predicted three candidate phage defense systems and multiple individual putative defense proteins in M. abscessus. Among them, Mab_2091, Mab_2092, and Mab_2093, designated CmaABC, are components of a cyclic oligonucleotide-based antiphage signaling system (CBASS) preventing TM4 infection. However, the inability of TM4 to form plaques even in CBASS-deficient M. abscessus implies the involvement of additional resistance mechanisms. Our findings underscore the challenges faced by mycobacteriophages in infecting M. abscessus, and highlight the complex interactions between this pathogen and its viral adversaries.